1991
DOI: 10.1002/jlb.49.1.98
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-γ Induced Resistance to Legionella pneumophila in Susceptible A/J Mouse Macrophages

Abstract: Legionella pneumophila (Lp) grow in cultures in human, guinea pig, and mouse macrophages from A/J strain mice. Because exudate macrophages from this strain of mice have been reported deficient in responsiveness to lymphokines, we thought it of interest to document the extent of responsiveness to interferon-gamma in the context of growth restriction of Lp. Peritoneal exudate macrophages were obtained from A/J mice and cultured in either the presence or absence of recombinant interferon-gamma. These cultures wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
34
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(40 citation statements)
references
References 0 publications
6
34
0
Order By: Relevance
“…Rather, the IFN-␥ transgene is likely exerting important activating effects on the resident leukocytes in the lungs. This argument is supported by previously published findings that recombinant IFN-␥ activates alveolar macrophages and other monocytes to limit the growth of intracellular Legionella organisms in vitro (3,15,33,37,43). Likewise, our observations indicated that macrophages isolated from AdmIFN-␥-treated mice inhibited the growth of Legionella.…”
Section: Discussionsupporting
confidence: 91%
“…Rather, the IFN-␥ transgene is likely exerting important activating effects on the resident leukocytes in the lungs. This argument is supported by previously published findings that recombinant IFN-␥ activates alveolar macrophages and other monocytes to limit the growth of intracellular Legionella organisms in vitro (3,15,33,37,43). Likewise, our observations indicated that macrophages isolated from AdmIFN-␥-treated mice inhibited the growth of Legionella.…”
Section: Discussionsupporting
confidence: 91%
“…Our observation that Legionella replication is restricted in IFN-␥-treated M is consistent with previous reports (23)(24)(25)51). Previous studies using M from A/J mice indicate that activated M restrict the growth of Legionella by a process that does not require production of reactive oxygen and nitrogen species and that is in part mediated by the sequestration of iron (51).…”
Section: Pgs Produced Upon Legionella Infection Of Activated Bm Inhibsupporting
confidence: 94%
“…Ex vivo treatment of murine M and human monocytes with IFN-␥ restricts the intracellular growth of Legionella (23)(24)(25). Studies using electron microscopy have suggested that Legionella are able to create an ER-like organelle within IFN-␥-activated M, but the bacteria are unable to replicate within this compartment (23).…”
Section: Activated Macrophages Infected Withmentioning
confidence: 99%
“…In previous studies, IFN-γ was shown to restrict L. pneumophila replication within A/J macrophages (9,19). Therefore, the effect of IFN-γ on the growth of the flaA mutant within C57BL/6 macrophages was of interest.…”
Section: Effects Of Recombinant Ifn-γ On C57bl/6 Macrophages Infectedmentioning
confidence: 96%